Iron Metabolism and Immune Regulation - Ni, Shuo; Yuan, Yin; Kuang, Yanbin; Li, Xiaolin (Frontiers in Immunology, 2022)
Iron is a critical element for living cells in terrestrial life. Although iron metabolism is strictly controlled in the body, disturbance of iron homeostasis under certain type of condition leads to innate and adaptive immune response. In innate immunity, iron regulates macrophage polarizations, neutrophils recruitment, and NK cells activity. In adaptive immunity, iron had an effect on the activation and differentiation of Th1, Th2, and Th17 and CTL, and antibody response in B cells. In this review, we focused on iron and immune regulation and listed the specific role of iron in macrophage polarization, T-cell activation, and B-cells antibody response. In addition, correlations between iron and several diseases such as cancer and aging degenerative diseases and some therapeutic strategies targeting those diseases are also discussed.